2009
DOI: 10.1148/radiol.2503081000
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial Microinfarction after Coronary Microembolization in Swine: MR Imaging Characterization

Abstract: Purpose:To use first-pass perfusion and delayed-enhanced (DE) magnetic resonance (MR) imaging for the detection of the early effects of coronary microembolization on myocardial perfusion and viability. Materials and Methods:Approval was obtained from the institutional committee on animal research. A hybrid x-ray and MR imaging system was used to guide the endovascular catheter and quantify the left anterior descending coronary artery (LAD) perfusion territory before microembolization and ischemic myocardium an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
63
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(64 citation statements)
references
References 51 publications
(82 reference statements)
0
63
1
Order By: Relevance
“…Eight adult healthy farm pigs (mean weight, 33 kg 6 1 [standard error of the mean ]) were anesthetized with a mixture of 2%-5% isofl urane and oxygen at a rate of 2-3 L/min, as described previously ( 8,9 ). Two animals died within 24 hours after delivery of the embolic materials.…”
Section: Study Protocol and Microembolimentioning
confidence: 99%
See 2 more Smart Citations
“…Eight adult healthy farm pigs (mean weight, 33 kg 6 1 [standard error of the mean ]) were anesthetized with a mixture of 2%-5% isofl urane and oxygen at a rate of 2-3 L/min, as described previously ( 8,9 ). Two animals died within 24 hours after delivery of the embolic materials.…”
Section: Study Protocol and Microembolimentioning
confidence: 99%
“…Microinfarcts are defi ned as bright heterogeneous subregions seen on delayed contrast material-enhanced MR images and pale unstained necrotic subregions seen on histochemically stained specimens (8)(9)(10)(11). In several studies, researchers found heterogeneous microinfarcts in patients ( 2,5,12,13 ) and animals (8-11) on delayed contrastenhanced MR images.…”
Section: Study Protocol and Microembolimentioning
confidence: 99%
See 1 more Smart Citation
“…13 The most common animals used for large animal models are rabbits, dogs, sheep, and pigs. The most frequent procedures used to induce left ventricular dysfunction include coronary ligation and microembolization, 14,15 which create permanent macrovascular and microvascular injury, respectively, and coronary balloon catheter occlusion for various durations, which results in ischemia reperfusion injury. 16,17 The advantages and disadvantages of various large animal models in ischemic cardiomyopathy are detailed in Table 1.…”
mentioning
confidence: 99%
“…18 Not surprisingly, the larger infarct sizes, however, resulted in a much higher mortality rate than observed in other models. [14][15][16][17]19 The question remains whether the benefit of larger infarct size outweighs the significant costs of over 50% mortality among instrumented animals.…”
mentioning
confidence: 99%